Operational Experiences with Flexible Transit Services - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2004)
TRB2019s Transit Cooperative Research Program (TCRP) Synthesis 53: Operational Experiences with Flexible Transit Services examines transit agency experiences with 201cflexible transit services,201d including all types of hybrid services that are not pure demand-responsive (including dial-a-ride and Americans with Disabilities Act paratransit) or fixed-route services, but that fall somewhere in between those traditional service models.

Utilization of Operational Environmental Satellite Data: Ensuring Readiness for 2010 and Beyond - National Research Council (The National Academies Press, 2004)

Improved Operational Testing and Evaluation and Methods of Combining Test Information for the Stryker Family of Vehicles and Related Army Systems: Phase II Report - National Research Council (The National Academies Press, 2004)
The U.S. Army Test and Evaluation Command (ATEC) is responsible for the operational testing and evaluation of Army systems in development. ATECrequested that the National Research Council form the Panel on Operational Test Design and Evaluation of the Interim Armored Vehicle (Stryker). The charge to this panel was to explore three issues concerning the IOT plans for the Stryker\/SBCT. First, the panel was asked to examine the measures selected to assess the performance and effectiveness of the Stryker\/SBCT in comparison both to requirements and to the baseline system. Second, the panel was asked to review the test design for the Stryker\/SBCT initial operational test to see whether it is consistent with best practices. Third, the panel was asked to identify the advantages and disadvantages of techniques for combining operational test data with data from other sources and types of use. In a previous report (appended to the current report) the panel presented findings, conclusions, and recommendations pertaining to the first two issues: measures of performance and effectiveness, and test design. In the current report, the panel discusses techniques for combining information.

Managing the Columbia River: Instream Flows, Water Withdrawals, and Salmon Survival - National Research Council (The National Academies Press, 2004)
Flows of the Columbia River, although modified substantially during the twentieth century, still vary considerably between seasons and between years. Lowest flows tend to occur during summer months when demand for irrigation water is at its highest and when water temperatures are greatest. These periods of low flows, high demand, and high temperature are critical periods for juvenile salmon migrating downstream through the Columbia River hydropower system. Although impacts on salmon of any individual water withdrawal may be small, the cumulative effects of numerous withdrawals will affect Columbia River flows and would pose increased risks to salmon survival. The body of scientific knowledge explaining salmon migratory behavior and physiology is substantial, but imperfect, and decision makers should acknowledge this and be willing to take action in the face of uncertainties. In order to provide a more comprehensive water permitting process, the State of Washington, Canada, other basin states, and tribal groups should establish a basin-wide forum to consider future water withdrawal application permits. If the State of Washington issues additional permits for water withdrawals from the Columbia River, those permits should contain provisions that allow withdrawals to be curtailed during critical high-demand periods.

Snow and Ice Control: Guidelines for Materials and Methods - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2004)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 526: Snow and Ice Control: Guidelines for Materials and Methods provides guidance for selecting roadway snow and ice control strategies, and tactics for a wide range of winter maintenance operating conditions. This guidance applies to highways, roads, streets, and other paved surfaces that carry motor vehicles2014under state or local jurisdictions.

Climate Data Records from Environmental Satellites: Interim Report - National Research Council (The National Academies Press, 2004)
The report outlines key elements to consider in designing a program to create climate-quality data from satellites. It examines historical attempts to create climate data records, provides advice on steps for generating, re-analyzing, and storing satellite climate data, and discusses the importance of partnering between agencies, academia, and industry. NOAA will use this report2014the first in a two-part study2014to draft an implementation plan for climate data records.

Convertible Roadways and Lanes - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2004)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 340: Convertible Roadways and Lanes examines the characteristics and operational requirements, costs, and benefits of convertible roadways and lanes.

Strategic Planning and Decision Making in State Departments of Transportation - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2004)
TRB2019s National Cooperative Highway Research Program (NCHRP) Synthesis 326: Strategic Planning and Decision Making in State Departments of Transportation examines state and provincial transportation departments' experience with strategic planning and synthesizes current approaches to linking strategic planning with other decision-making processes, including operational and tactical planning, resource allocation, performance management, and performance measurement.

Individual Differences and the "High-Risk" Commercial Driver - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2004)
TRB's Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 4: Individual Differences and the 201cHigh-Risk201d Commercial Driver explores individual differences among commercial drivers, particularly as these differences relate to the 201chigh-risk201d commercial driver. The synthesis identifies factors relating to commercial vehicle crash risk and assesses ways that the high-risk driver can be targeted by various safety programs and practices, at both fleet- and industry-wide levels.

Naval Forces' Defense Capabilities Against Chemical and Biological Warfare Threats - National Research Council (The National Academies Press, 2004)
U.S. naval forces must be prepared to respond to a broad array of threats. Of increasing importance are those from chemical and biological warfare (CW and BW). To help review its current state of preparedness, the Chief of Naval Operations asked the National Research Council (NRC) to assess the U.S. Navy2019s defense capabilities against CW and BW threats. In particular to what extent are they being developed to enable naval forces to sense and analyze quickly the presence of chemical and biological agents, withstand or avoid exposure to such agents, deal with contamination under a broad spectrum of operational conditions, and over what period will these capabilities be realized. This report presents the results of that assessment. It provides an overview of the potential threats, and an evaluation of the Navy2019s operations, non-medical programs, and medical countermeasures designed to confront those threats. The report also presents a series of general and specific findings and recommendations based on these assessments.

Improving the Characterization Program for Contact-Handled Transuranic Waste Bound for the Waste Isolation Pilot Plant - National Research Council (The National Academies Press, 2004)
As operational experience is gained in the disposal of transuranic waste from nuclear weapons facilities at the Waste Isolation Pilot Plant in New Mexico, the Department of Energy (DOE) has opportunities to change how it 201ccharacterizes201d waste to confirm that it is appropriate for shipment to and disposal at the underground repository. The waste shipped to the facility includes gloves, rags, tools, and other debris or dried sludge that has been contaminated by radioactive elements, including plutonium, during production or cleanup activities in the DOE weapons complex. However, before the DOE seeks regulatory approval for changes to its characterization program, the agency should conduct and publish a systematic and quantitative assessment to show that the proposed changes would not affect the protection of workers, the public, or the environment, according to the committee. The assessment should take into account technical factors, societal and regulatory impacts, and the time and effort required to make the changes.

Effects of Degraded Agent and Munitions Anomalies on Chemical Stockpile Disposal Operations - National Research Council (The National Academies Press, 2004)
The U.S. Army is in the process of destroying its entire stock of chemical weapons. To help with stockpile disposal, the Army2019s Chemical Stockpile Disposal Program (CSDP), in 1987, asked the National Research Council (NRC) for scientific and technical advice. This report is one in a series of such prepared by the NRC over the last 16 years in response to that request. It presents an examination of the effect of leaking munitions (leakers) and other anomalies in the stored stockpile on the operation of the chemical agent disposal facilities. The report presents a discussion of potential causes of these anomalies, leaker tracking and analysis issues, risk implications of anomalies, and recommendations for monitoring and containing these anomalies during the remaining life of the stockpile.

Review of the Army's Technical Guides on Assessing and Managing Chemical Hazards to Deployed Personnel - National Research Council (The National Academies Press, 2004)
To guide mission planning, military decision makers need information on the health risks of potential exposures to individual soldiers and their potential impact on mission operations. To help with the assessment of chemical hazards, the U.S. Army Center for Health Promotion and Preventive Medicine developed three technical guides for characterizing chemicals in terms of their risks to the mission and to the health of the force. The report reviews these guides for their scientific validity and conformance with current risk-assessment practices. The report finds that the military exposure guidelines are appropriate (with some modification) for providing force health protection, but that for assessing mission risk, a new set of exposure guidelines is needed that predict concentrations at which health effects would degrade the performance of enough soldiers to hinder mission accomplishment.

Reengineering the 2010 Census: Risks and Challenges - National Research Council (The National Academies Press, 2004)
At the request of the U.S. Census Bureau, the National Research Council2019s Committee on National Statistics established the Panel on Research on Future Census Methods to review the early planning process for the 2010 census. This new report documents the panel2019s strong support for the major aims of the Census Bureau2019s emerging plan for 2010. At the same time, it notes the considerable challenges that must be overcome if the bureau2019s innovations are to be successful. The panel agrees with the Census Bureau that implementation of the American Community Survey and, with it, the separation of the long form from the census process are excellent concepts. Moreover, it concurs that the critically important Master Address File and TIGER geographic systems are in dire need of comprehensive updating and that new technologies have the potential to improve the accuracy of the count. The report identifies the risks and rewards of these and other components of the Census Bureau2019s plan. The report emphasizes the need for the bureau to link its research and evaluation efforts much more closely to operational planning and the importance of funding for a comprehensive and rigorous testing program before 2010.

An Assessment of the Small Business Innovation Research Program: Project Methodology - National Research Council (The National Academies Press, 2004)
In response to a Congressional mandate, the National Research Council conducted a review of the SBIR program at the five federal agencies with SBIR programs with budgets in excess of 100 million (DOD, NIH, NASA, DOE, and NSF). The project was designed to answer questions of program operation and effectiveness, including the quality of the research projects being conducted under the SBIR program, the commercialization of the research, and the program's contribution to accomplishing agency missions. This report describes the proposed methodology for the project, identifying how the following tasks will be carried out: 1) collecting and analyzing agency databases and studies; 2) surveying firms and agencies; 3) conducting case studies organized around a common template; and 4) reviewing and analyzing survey and case study results and program accomplishments. Given the heterogeneity of goals and procedures across the five agencies involved, a broad spectrum of evaluative approaches is recommended.

Biological Confinement of Genetically Engineered Organisms - National Research Council (The National Academies Press, 2004)
Genetically engineered organisms (GEOs) have been under development for more than 20 years while GE crops have been grown commercially during the last decade. During this time, a number of questions have cropped up concerning the potential consequences that certain GEOs might have on natural or managed ecosystems and human health. Interest in developing methods to confine some GEOs and their transgenes to specifically designated release settings has increased and the success of these efforts could facilitate the continued growth and development of this technology. Biological Confinement of Genetically Engineered Organisms examines biological methods that may be used with genetically engineered plants, animals, microbes, and fungi. Bioconfinement methods have been applied successfully to a few non-engineered organisms, but many promising techniques remain in the conceptual and experimental stages of development. This book reviews and evaluates these methods, discusses when and why to consider their use, and assesses how effectively they offer a significant reduction of the risks engineered organisms can present to the environment. Interdisciplinary research to develop new confinement methods could find ways to minimize the potential for unintended effects on human health and the environment. Need for this type of research is clear and successful methods could prove helpful in promoting regulatory approval for commercialization of future genetically engineered organisms.

Burning Plasma: Bringing a Star to Earth - National Research Council (The National Academies Press, 2004)
Significant advances have been made in fusion science, and a point has been reached when we need to decide if the United States is ready to begin a burning plasma experiment. A burning plasma2014in which at least 50 percent of the energy to drive the fusion reaction is generated internally2014is an essential step to reach the goal of fusion power generation. The Burning Plasma Assessment Committee was formed to provide advice on this decision. The committee concluded that there is high confidence in the readiness to proceed with the burning plasma step. The International Thermonuclear Experimental Reactor (ITER), with the United States as a significant partner, was the best choice. Once a commitment to ITER is made, fulfilling it should become the highest priority of the U.S. fusion research program. A funding trajectory is required that both captures the benefits of joining ITER and retains a strong scientific focus on the long-range goals of the program. Addition of the ITER project will require that the content, scope, and level of U.S. fusion activity be defined by program balancing through a priority-setting process initiated by the Office of Fusion Energy Science.

Assessing the National Streamflow Information Program - National Research Council (The National Academies Press, 2004)
From warning the public of impending floods to settling legal arguments over water rights, the measurement of streamflow (201cstreamgaging201d) plays a vital role in our society. Having good information about how much water is moving through our streams helps provide citizens with drinking water during droughts, control water pollution, and protect wildlife along our stream corridors. The U.S. Geological Survey2019s (USGS) streamgaging program provides such information to a wide variety of users interested in human safety, recreation, water quality, habitat, industry, agriculture, and other topics. For regional and national scale streamflow information needs, the USGS has created a National Streamflow Information Program (NSIP). In addition to streamgaging, the USGS envisions intensive data collection during floods and droughts, national assessments of streamflow characteristics, enhanced information delivery, and methods development and research. The overall goals of the program are to: meet legal and treaty obligations on interstate and international waters, support flow forecasting; measure river basin outflows, monitor sentinel watersheds for long-term trends in natural flows, and measure flows for water quality needs. But are these the right topics to collect data on? Or is the USGS on the wrong track? In general, the book is supportive of the design and content of NSIP, including its goals and methodology for choosing stream gages for inclusion in the program. It sees the ultimate goal of NSIP as developing the ability to use existing data-gathering sites to generate streamflow information with quantitative confidence limits at any location in the nation. It is just as important to have good measurements during droughts as during floods, and it therefore recommends supporting Natural Resource Conservation Service forecast sites in addition to those of the National Weather Service.

Identification of Research Needs Related to Highway Runoff Management - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Report 521: Identification of Research Needs Related to Highway Runoff Management summarizes significant stormwater management practices and research efforts, and it identifies the most pressing gaps and needs in the current state of knowledge in over more than 30 subject areas. The report includes full research project statements for the topics considered to be of highest priority.

Academic Health Centers: Leading Change in the 21st Century - Institute of Medicine (The National Academies Press, 2004)
Academic health centers are currently facing enormous changes that will impact their roles in education, research, and patient care. The aging and diversity of the population will create new health care needs and demands, while rapid advances in technology will fundamentally alter the health care systems2019 capabilities. Pressures on health care costs, growth of the uninsured, and evidence of quality problems in health care will create a challenging environment that demands change. Academic Health Centers explores how AHCs will need to consider how to redirect each of their roles so they are able to meet the burgeoning challenges of health care and improve the health of the people they serve. The methods and approaches used in preparing health professionals, the relationship among the variety of their research programs and the design of clinical care will all need examination if they are to meet the changing demands of the coming decades. Policymakers will need to create incentives to support innovation and change in AHCs. In response, AHCs will need to increase the level of coordination and integration across their roles and the individual organizations that comprise the AHC if they are to successfully undertake the types of changes needed. Academic Health Centers lays out a strategy to start a continuing and long-term process of change.